A QoE-aware joint resource allocation algorithm for uplink carrier aggregation in LTE-Advanced systems - Yujae Song; Youngnam Han; Yonghoon Choi (2014 IEEE International Conference on Communications (ICC), 2014)
Carrier aggregation (CA) is an essential feature in the Long Term Evolution-Advanced (LTE-A) system, which can aggregate two and more component carriers (CCs) to form a much wider transmission bandwidth up to 100 MHz. By means of CA, a user equipment (UE) can be scheduled on multiple CCs simultaneously to transmit data traffic. Recently, the studies on the efficient operation of an LTE-A based CA system have received much attention under simultaneous access scenarios for multiple CCs. However, the existing literature lacks efforts on Quality of Experience (QoE)-aware CA, especially in the uplink. In this paper, we propose a joint resource allocation algorithm for an uplink LTE-A based system, focusing on QoE-aware CA. We first present a framework for the evaluation of UE's QoE satisfaction level by designing a link reward, resource cost, and link utility function. Then, a QoE-aware joint resource allocation algorithm is proposed for the efficient sharing of radio resource by UEs, so that uplink system utility is maximized. Numerical results demonstrate the validity of the proposed algorithm.